Novel Expansions of the Gene Encoding Dihydropteroate Synthase in Trimethoprim-Sulfamethoxazole-Resistant Streptococcus pneumoniae - Padayachee, Thanugarani (American Society for Microbiology, 1999)
A study of eight sulfonamide-resistant clinical isolates of Streptococcus pneumoniae revealed chromosomal mutations within the gene encoding dihydropteroate synthase that play a role in conferring resistance to sulfamethoxazole. The presence of the suld mutation, found previously only in a laboratory mutant, was shown to occur in three of the wild-type clinical isolates. The duplication of Ser(61), the other previously defined mutation in the dihydropteroate synthase gene of S. pneumoniae, was observed in only one of the isolates characterized. We report two previously unidentified amino acid alterations, namely, a duplication of Arg(58) and Pro(59) and an insertion of an arginine residue between Gly(60) and Ser(61) in trimethoprim-sulfamethoxazole-resistant strains. The significance of these mutations was confirmed by site-directed mutagenesis and by the transformation of a susceptible strain of S. pneumoniae to sulfamethoxazole resistance. Two resistant isolates did not contain any mutations within the gene encoding dihydropteroate synthase. The results presented suggest the independent generation of resistant mutations among South African clinical isolates. It is also proposed that the mechanism of sulfonamide resistance in S. pneumoniae involves the expansion of a specific region within dihydropteroate synthase, which probably forms part of the sulfonamide binding site.